Ear Acupressure for Allergic Rhinitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (3rd May 2021) - Zhong, Juan; Liu, Shuqin; Lai, Dan; Lu, Tao; Shen, Yifeng; Gong, Qisheng; Li, Peijia; Zhang, Qinxiu
Abstract : Background . The treatment effects and safety of ear acupressure (EAP) for patients with allergic rhinitis (AR) have yet to be clarified. Objective . To evaluate the effects and safety of EAP in AR patients. Design . Systematic review of published studies. Methods . A total of 24 English and Chinese databases (PubMed, EMBASE (Excerpta Medical Database), Cochrane Central Register of Controlled Trials, CINAHL, Informit, ScienceDirect, LILACS (Latin American and Caribbean Health Sciences), ProQuest, AMED, Blackwell Synergy, PsycINFO, Panteleimon, AcuBriefs, KoreaMed, IndMed, Ingenta, mRCT, ISI Web of Knowledge, ERIC, VIP Information (http://www.cqvip .com), China National Knowledge Infrastructure (http://www.cnki.net ), Cochrane Library, Chinese Cochrane Centre Controlled Trials Register Platform, and Wanfang Chinese Digital Periodical and Conference Database) were searched from their respective inceptions to August 2020 to collect randomized controlled trials of ear acupressure for allergic rhinitis. We performed literature inclusion, data extraction, and trial quality evaluations. Methodological quality was assessed according to the Cochrane Handbook. Revman5.3 was used for all analyses. Results . A total of 203 trials were identified and eleven studies involved 1094 participants aged 3–70 years. EAP was better than control group interventions in terms of effectiveness (risk ratio (RR): 0.51; 95% confidence interval (CI): 0.36–0.70; P < 0.0001 ). EAP was superior to sham EAP in terms of improvement of the total nasal symptom score (RR: −0.50; 95% CI: −0.96–0.05; P = 0.03), sneezing score (RR: −0.36; 95% CI: −0.59–0.12; P = 0.003), global QoL score (RR: 0.42; 95% CI: 0.04–0.08; P = 0.03), and eye symptom score (RR: −0.36; 95% CI: −0.67–0.05; P = 0.02). Conclusions . Despite the positive results, it is premature to confirm the efficacy of EAP for treating AR. More high-quality studies are needed to confirm safety and efficacy.